Fusarium Wilt (Fusarium oxysporum f. sp. niveum) of Watermelon - Pamela Roberts; Nicholas Dufault; Robert Hochmuth; Gary Vallad; Mathews Paret (EDIS)
Fusarium wilt of watermelon is one of the most serious and difficult diseases to manage and occurs in most production regions worldwide. The fungus can be seedborne and has great longevity in the soil, allowing infested soil to also serve as a source of infection. This new 4-page publication of the UF/IFAS Plant Pathology Department signs, symptoms, and the disease cycle of Fusarium wilt and provides recommendations for cultural and chemical management. Written by Pamela Roberts, Nicholas Dufault, Robert Hochmuth, Gary Vallad, and Mathews Paret. https://edis.ifas.ufl.edu/pp352